Management of Pink Spot due to Class IV Invasive Cervical Root Resorption using Vital Pulp Therapy: A Case Report - Asgary, Saeed (Iranian Endodontic Journal, 2023)
A 30-year-old male patient with the chief complaint of pink spot discoloration of the tooth crown in his upper left central incisor was referred for endodontic and esthetic management. After thorough clinical and radiographic examinations, the final diagnosis was class IV invasive cervical resorption (ICR) which was conservatively treated with an orthograde approach; i.e. vital pulp therapy with calcium-enriched mixture cement (VPT/CEM). The use of VPT/CEM was successful to restore esthetics and stop the ICR; confirmed clinically, radiographically, and tomographically at one-year recall. The above-mentioned minimally invasive approach reported in the current case study may be considered a practical treatment modality for ICR, specifically in anterior teeth.